Value-Based and Context-Aware Selection of Software-Service Bundles: A Capability Based Method - Jānis Grabis; Kurt Sandkuhl (Complex Systems Informatics and Modeling Quarterly)
In many application areas, vendors offer to their clients combinations of software products and services, which can be considered as software-service bundles. The clients select a combination of software product and associated service best suited to their individual requirements and circumstances. The bundle usually has to be configured by the vendor to fit the specific situation of the client. When circumstances change, the software-service bundle or its configuration need adaptation. The article proposes a method helping clients to select the most appropriate combination or configuration. The method is based on information sharing between the vendor and client and also supports the continuous improvement of the solution in response to changing circumstances. The method applies principles and techniques of the Capability Driven Development to specify performance objectives and contextual factors affecting delivery of a software-service bundle. Application of the method is shown using an illustrative case of a data processing service from utility industries.